Revenue Administration : Performance Measurement in Tax Administration - Crandall, William Joseph (Washington, D.C. : International Monetary Fund, 2010)
This technical note describes measuring performance in tax administration. Performance measurement is an ongoing process of ascertaining how well, or how poorly, an organization is achieving its goals and objectives. It involves the continuous collection of data on progress made in this regard. Performance indicators, or measures, are developed as standards for assessing the extent to which these objectives are achieved. This note explains key features of performance management and performance measurement. It outlines how tax administrations can apply performance management at the strategic level. Key tasks in implementing a performance management system are also described.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet